1998
DOI: 10.1055/s-2007-973558
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Neonatal Cranial Ultrasound, MRI in Infancy and Neurodevelopmental Outcome in Infants with a Large Intraventricular Haemorrhage with or without Unilateral Parenchymal Involvement

Abstract: Combining neonatal US with MRI in infancy enhances our understanding of the long-term effects of severe haemorrhagic brain lesions, occurring in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 1 publication
0
27
0
1
Order By: Relevance
“…44 Moreover, abnormalities of MRI signals from the posterior parietal periventricular crossroad in older preterm infants may have a prognostic value for evaluating the outcome of perinatal PVL. 45 Another interesting finding, frequently observed in survivors of very preterm birth 46,47 and after the perinatal PVL, [48][49][50] is the significant reduction of the corpus callosum. As callosal fibres represent a substantial component of periventricular crossroads, 3 it is not surprising that hypoxic-ischaemic lesions of the corpus callosum represent both an essential component of selective vulnerability of periventricular pathways as well as a frequent abnormality of corticocortical connections.…”
Section: Comparison Of Mri and Histological Findingsmentioning
confidence: 99%
“…44 Moreover, abnormalities of MRI signals from the posterior parietal periventricular crossroad in older preterm infants may have a prognostic value for evaluating the outcome of perinatal PVL. 45 Another interesting finding, frequently observed in survivors of very preterm birth 46,47 and after the perinatal PVL, [48][49][50] is the significant reduction of the corpus callosum. As callosal fibres represent a substantial component of periventricular crossroads, 3 it is not surprising that hypoxic-ischaemic lesions of the corpus callosum represent both an essential component of selective vulnerability of periventricular pathways as well as a frequent abnormality of corticocortical connections.…”
Section: Comparison Of Mri and Histological Findingsmentioning
confidence: 99%
“…Consequent periventricular venous infarction is often hemorrhagic and may damage the descending corticospinal tracts, resulting in hemiparesis. 23 Previous studies have shown that periventricular venous infarction can occur also prenatally and can be detected in term born children. 16 In a case series supplied with a literature review of prenatally developed hemorrhages, the mean age of prenatal hemorrhages was 30 gestational weeks with a range of 20-37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The clot itself may obscure the ventricle due to complete filling of the lumen. IVH may or may not be associated with an intra parenchymal haemorrhage [16].…”
Section: Pitfalls Of Usg Studymentioning
confidence: 99%